Creating the learning object structure for the introduction to informatics course - Dapkūnas, Sigitas; Lapin, Kristina (Lietuvos matematikos rinkinys, 2005)
The paper dealswith creation of the learning object repository for the course of introduction to informatics. Existing courses are based on instructional materials, prepared by lecturers. Most of them are traditional lecture notes. Only one of four instructional materials is in the form of Web pages. These LO are used in several courses and could be a base of the future repository. The structure of the courses is analysed and missing LO are ascertained.
Keywords: learning paradigm; instructional material; learning object